Saudi English language teachers’ pre-service education: How effective is it? - Al-Mohanna, Ayedh Dhawi (International Journal of Publication and Social Studies, 2024)
This study aims to examine the pre-service education of English as a foreign language (EFL) teachers in the context of Saudi Arabian education. The research methodology adopts a qualitative approach, incorporating document analysis and interviews as means of data collection. The document analysis is employed to elucidate the objectives and substance of the EFL teacher pre-service education program. The interviews are conducted to investigate EFL teachers’ perspectives regarding their experiences as applicants in the EFL teacher pre-service education programs provided by English departments at Saudi universities. The target population of this study is a group of male teachers who graduated from Saudi universities with a bachelor’s degree in English and currently teach English as a foreign language in Saudi public schools (elementary, intermediate, and secondary levels). A total of 112 EFL teachers participated in the study. Their teaching experiences range from 2 to 4 years. They graduated from different Saudi universities. This study indicates that the pre-service education for Saudi EFL instructors is insufficient in adequately preparing and equipping English teachers with the necessary knowledge and skills for their professional requirements. Therefore, it is essential to enhance pre-service education to offer the best possible support to its candidates. The study presents several recommendations and suggestions to guarantee the efficacy of EFL teacher pre-service education in the Saudi Arabian context.